2019
DOI: 10.1021/acssuschemeng.9b03367
|View full text |Cite
|
Sign up to set email alerts
|

How to Turn Yeast Cells into a Sustainable and Switchable Biocatalyst? On-Demand Catalysis of Ketone Bioreduction or Acyloin Condensation

Abstract: In this study, yeast strains were screened and immobilized in a form preserving the multifaceted biocatalytic activity. Immobilization of the silica-supported whole cells of various yeasts, such as Lodderomyces elongisporus, Pichia carsonii, Candida norvegica, and Debaryomyces fabryi, by sol−gel entrapment resulted in easy-to-handle biocatalysts that mediated efficiently different types of synthetic reactions. In the present study, the enantiotope selective reduction of prochiral ketones 1a−d and the acyloin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Immobilized microorganisms are able to effectively dispose of organic compounds such as 4-phenylbutan-2-amine or heptan-2-amine [ 107 ] in a continuous flow mode. At the same time, selective reduction of prochiral ketones and acyloin condensation of benzaldehyde with yields from moderate 20% to great 99% were observed during the joint immobilization of yeast cells of Lodderomyceselongisporus , Pichia carsonii , Candida norvegica , and Debaryomyces fabryi in a sol-gel matrix [ 108 ].…”
Section: Classification Of Hybrid Materials According To the Applicat...mentioning
confidence: 99%
“…Immobilized microorganisms are able to effectively dispose of organic compounds such as 4-phenylbutan-2-amine or heptan-2-amine [ 107 ] in a continuous flow mode. At the same time, selective reduction of prochiral ketones and acyloin condensation of benzaldehyde with yields from moderate 20% to great 99% were observed during the joint immobilization of yeast cells of Lodderomyceselongisporus , Pichia carsonii , Candida norvegica , and Debaryomyces fabryi in a sol-gel matrix [ 108 ].…”
Section: Classification Of Hybrid Materials According To the Applicat...mentioning
confidence: 99%
“…However, because of weaker binding forces involved in immobilisation, deactivation of the enzyme by conformational distortions is less likely in comparison with other approaches. Entrapment of ADHs with various gelating materials comprising silica gels (Musa et al, 2007;Nagy-Gyor et al, 2018;Liu et al, 2019;Nagy-Győr et al, 2019) polyvinyl alcohol (Krasnan et al, 2016;Petrovicova et al, 2018;Yildirim et al, 2019) poly ethyleneglycol (Schmieg et al, 2019) superabsorbers (Heidlindemann et al, 2014;Adebar and Groger, 2020), alginates (Milagre et al, 2005(Milagre et al, , 2006He et al, 2017;Nasario et al, 2019), metal organic frameworks (MOFs) (Carucci et al, 2018;Ye et al, 2020) or liposomes (Yoshimoto et al, 2008) has been reported.…”
Section: Adh Immobilisationmentioning
confidence: 99%
“…In addition to the use of purified and immobilized enzyme preparations, biocatalysis can be pursued with intact cells [3,16–18] . In the case of yeast, the cells may be available commercially at near‐negligible costs.…”
Section: Introductionmentioning
confidence: 99%